The Alabaster Ceiling: The Gender Legacy of the Papal States - Elona Harka; Luca Nunziata; Lorenzo Rocco (Institute of Labor Economics (IZA), 2021)
We investigate the legacy of the former Papal States on modern female condition by comparing Italian municipalities located in a narrow band across the border between the former Papal States and the former Grand Duchy of Tuscany. While in the Papal States gender inequality was particularly severe, the Grand Duchy of Tuscany experienced a relatively stronger female emancipation. We find that one century after the fall of the Papal States, in the municipalities formerly ruled by the Pope, there is lower female labour market participation and employment when compared to their counterparts in Tuscany, while we do not detect any discontinuity for males. We also find that in the former Papal States there is less political support for the legal right to divorce, historically advocated by women emancipation movements.
Keywords: N9; J12; P48; Z12; Z13; 330; papal states; gender equality; female condition; divorce; religion; labour